Coccolithophores and the Continuous Plankton Recorder Survey - Graeme Hays; A Warner; A John; D Harbour; P Holligan (1995)
Samples historically collected and analysed by the Continuous Plankton Recorder (CPR) survey were used to describe the distribution of coccolithophores (class Prymnesiophyceae) in the north-east Atlantic and the North Sea. In the routine CPR analysis, members of this group are simply identified as ‘coccolithophores’ and not to any further taxonomic level. From this analysis, the 200-m depth contour marked a point of distinct transition between high coccolithophore occurrence (off the shelf) and low coccolithophore occurrence (on the shelf). Thirty-three CPR samples that had been collected between 1979–1992, were re-examined and the coccolithophores identified to a more detailed taxonomic level. Among the species identified was the bloom-forming coccolithophore, Emiliania huxleyi. Thus archived CPR samples could potentially be re-analysed to assess regional, seasonal and decadal changes in the occurrence of this species.